2021
DOI: 10.1016/j.pan.2021.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of CD70 expression in resected pancreatic cancer: Prognostic value and therapeutic potential

Abstract: BackgroundAberrant expression of CD70 in several malignancies is potentially associated with poor patient prognosis and could serve as a therapeutic target. However, the clinical relevance of CD70 expression in pancreatic cancer has not been thoroughly explored. MethodsWe evaluated CD70 expression in 166 surgical specimens obtained from human patients with pancreatic cancer. We analyzed the function of CD70 in proliferation and migration using pancreatic cancer cell lines with silenced CD70 expression. Results… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
(64 reference statements)
1
4
0
Order By: Relevance
“…To follow, we show that CD70 silencing significantly reduce tumor burden and volume, and significantly increases survival time, with some animals showing no signs of disease up until the end of the experiment. These data represent similar findings to that seen in the literature, indicating that CD70 may play a crucial role in tumor-initiating cells in multiple cancers (Liu et al 2018;Nakamura et al 2021). To better understand the cellular pathways and programs involving CD70, we carried out GSEA using RNAseq of our CD70-silenced cell lines.…”
Section: Discussionsupporting
confidence: 87%
“…To follow, we show that CD70 silencing significantly reduce tumor burden and volume, and significantly increases survival time, with some animals showing no signs of disease up until the end of the experiment. These data represent similar findings to that seen in the literature, indicating that CD70 may play a crucial role in tumor-initiating cells in multiple cancers (Liu et al 2018;Nakamura et al 2021). To better understand the cellular pathways and programs involving CD70, we carried out GSEA using RNAseq of our CD70-silenced cell lines.…”
Section: Discussionsupporting
confidence: 87%
“…These data represent similar findings to that seen in the literature, indicating that CD70 may play a crucial role in tumor-initiating cells in multiple cancers. 105 106 To better understand the cellular pathways and programs involving CD70, we carried out GSEA using RNAseq of our CD70-silenced cell lines. We were able to contribute to the functional understanding of CD70 by showing that, as previously noted in RCC and other cancers, CD70 plays a role in controlling hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Upon silencing of CD70 in glioblastoma cell lines, expression levels of EMT-associated genes, SOX2 and CD44, decreased, resulting in inhibition of tumor growth and migration [95]. In addition, it was shown that β-catenin was significantly reduced after siRNA-mediated knock-down of CD70 expression in human pancreatic cell lines, as well as other EMT-related genes, such as Vimentin, Snail and Slug [97]. In melanoma, CD70 expression led to MAPK activation and RhoE overexpression, thereby promoting tumor migration [91].…”
Section: Signaling In Solid Tumorsmentioning
confidence: 99%